Sexual identity, earnings and labor market dynamics: new evidence from longitudinal data in Australia - Sabia, Joseph J; Wooden, Mark; Nguyen, Thanh Tam (My University, 2017)
Using newly collected data on sexual identity from the Household, Income and Labour Dynamics in Australia Survey, this study examines the relationship between sexual identity and labour market outcomes. Our findings show that gay males are: (i) less likely to be continuously employed than their heterosexual counterparts, and (ii) face an annual earnings penalty of 16–21%. There are also important differences in earnings dynamics for men who transition into (or out of) same-sex versus opposite-sex live-in relationships. Individual fixed effects estimates show that opposite-sex partnerships are associated with increased earnings for men, while same-sex partnerships are associated with small declines in earnings that are statistically indistinguishable from zero. For women, we find evidence of an earnings premium for lesbians, driven largely by increased labour supply on the intensive margin.
Southern Economic Journal
Keywords: Gender; Identity; Labour market